Caracterización de los resultados de la competencia en inglés del examen Saber Pro en los programas de Fonoaudiología en Colombia en los años 2016–2022 - Angie Tamara Duque-Barrera; Andrés Llanos-Redondo; Andreina Constanza Antolínez-Vera; Edwin Mauricio Portilla-Portilla; Nixon Albeiro Zambrano-Medina (Mundo Fesc)
Background: The inclusion of English proficiency in higher education is based on the demands of globalization and contributes to national development; this demands changes in the training processes carried out in universities. Objective: To characterize the results of the English proficiency exam of the Saber Pro Exam in Speech Therapy programs in Colombia between 2016 and 2022. Methods: A quantitative research with a descriptive scope; an analysis was carried out of the results of the Saber Pro Exam of English proficiency in Speech Therapy programs from 2016 to 2022, published by the Colombian Institute for the Evaluation of Education (ICFES). Results: The English proficiency of the 15 Speech Therapy Programs between 2016 and 2022 showed an average of 151.06, with a maximum score of 190.00 and a minimum of 129.00. universities have an average of 154.84, with a maximum grade of 200.00 and a minimum of 124.00. In the case of the reference group, the average is 149.18, with a maximum score of 154.00 and a minimum of 143.00. The Saber Pro exam becomes a metric that evolves over time and is used to examine the rise or decline in quality, the English proficiency of Speech Therapy programs showed an average that is slightly below the university . Conclusions: According to the Common European Framework, speech therapy programs are mostly at levels A1-A2. Therefore, the need to give greater importance to second language learning in educational institutions becomes evident.